Pengaruh Metode Pembelajaran The Power of Two terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas V SD Dharma Karya UT - Abizar Al Ghiffari, Rayhan; Ediana Latip, Asep (Minhaj Pustaka, 2025)
ABSTRACT This study aims to determine the effect oflearning method on learning the power of two outcomes in social studies class V SD Dharma Karya UT. This study used a quasi-experimental quantitative research method with a design control group pre-test and post-test design with a research population of 55 students and a research sample of 32 students. The research sample was taken from class V-1 as the experimental class totaling 16 students and class V-2 as the control class as many as 16 students. The variables in this study consisted of method the power of two as the independent variable and learning outcomes as the dependent variable. The method used in this study is a learning outcome test totaling 30 items. Based on the results of the normality test, it was obtained that thesignificance value posttest in the control class was 0.273 > 0.05, which means that the data were normally distributed. Likewise, thesignificance value posttest in the experimental class is 0.063 > 0.05, which means the data is normally distributed. Meanwhile, based on the results of the homogeneity test, the data showed that the significance value of posttest the control class and experimental class was a mean of 0.090 and a median of 0.085. If the value is Sig. ≥ 0.05, then 0.090 > 0.05 < 0.085, which means that thescores for posttest the control class and the experimental class come from a homogeneous population or the same variety. Based on the results of the hypothesis test (t-test), the value data for the posttest control class and experimental class met the criteria (Sig. (2-tailed)) > 0.05, namely 0.007 < 0.025. This means that the null hypothesis (Ho) is rejected and hypothesis one (Ha) is accepted. Then it can be concluded that Ha: There is a significant difference between theresults of posttest the control class and the experimental class, it can be concluded that there is a significant effect ofmethod the power of two on learning outcomes in social studies subjects for fifth grade students of SD Dharma Karya UT. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh metode pembelajaran the power of two terhadap hasil belajar pada mata pelajaran IPS kelas V SD Dharma Karya UT. Penelitian ini menggunakan metode penelitian kuantitatif eksperimen semu dengan desain control group pre-test and post-test design dengan populasi penelitian sebanyak 55 siswa dan sampel penelitian sebanyak 32 siswa. Sampel penelitian ini diambil dari kelas V-1 sebagai kelas eksperimen berjumlah 16 siswa dan kelas V-2 sebagai kelas kontrol sebanyak 16 siswa. Variabel dalam penelitian ini terdiri dari metode the power of two sebagai variabel bebas dan hasil belajar sebagai variabel terikat. Metode yang digunakan dalam penelitian ini adalah tes hasil belajar berjumlah 22 butir soal. Berdasarkan hasil uji normalitas diperoleh data bahwa nilai signifikasi posttest pada kelas kontrol yaitu 0,273 > 0,05 yang berarti data berdistribusi normal. Begitu pula nilai signifikasi posttest pada kelas eksperimen yaitu 0,063 > 0,05 yang berarti data berdistribusi normal. Sedangkan berdasarkan hasil uji homogenitas diperoleh data bahwa nilai signifikasi posttest kelas kontrol dan kelas eksperimen yaitu mean sebesar 0,090 dan median sebesar 0,085. Jika nilai Sig. ≥ 0,05 maka 0,090 > 0,05 < 0,085, yang artinya perolehan nilai posttest kelas kontrol dan kelas eksperimen berasal dari populasi yang homogen atau ragam yang sama. Adapun berdasarkan hasil uji hipotesis (uji-t) diperoleh data nilai posttest kelas kontrol dan kelas eksperimen memenuhi kriteria (Sig. (2-tailed)) > 0,05 yaitu 0,007 < 0,025. Artinya hipotesis nol (Ho) ditolak dan hipotesis satu (Ha) diterima. Maka dapat disimpulkan bahwa Ha: terdapat perbedaan signifikan antara hasil posttest kelas kontrol dan kelas eksperimen, artinya terdapat pengaruh yang signifikan metode the power of two terhadap hasil belajar pada mata pelajaran IPS siswa kelas V SD Dharma Karya UT.